Inhibition of Topoisomerase (DNA) I (TOP1): DNA Damage Repair and Anticancer Therapy - Xu, Yang (Biomolecules, 2015)
Most chemotherapy regimens contain at least one DNA-damaging agent that preferentially affects the growth of cancer cells. This strategy takes advantage of the differences in cell proliferation between normal and cancer cells. Chemotherapeutic drugs are usually designed to target rapid-dividing cells because sustained proliferation is a common feature of cancer [1,2]. Rapid DNA replication is essential for highly proliferative cells, thus blocking of DNA replication will create numerous mutations and/or chromosome rearrangements—ultimately triggering cell death [3]. Along these lines, DNA topoisomerase inhibitors are of great interest because they help to maintain strand breaks generated by topoisomerases during replication. In this article, we discuss the characteristics of topoisomerase (DNA) I (TOP1) and its inhibitors, as well as the underlying DNA repair pathways and the use of TOP1 inhibitors in cancer therapy.